Effects Of Exercise On Executive Functions During A Simulated Extravehicular Activity (EVA) Underwater...2021 ACSM Annual Meeting & World Congresses [Virtual], June 1 -5, 2021 - Möller, Fabian; Hoffmann, Uwe; Vogt, Tobias; Steinberg, Fabian (Medicine & Science in Sports & Exercise)
PURPOSE: Extra-vehicular activities (EVA) in space performed by humans in microgravity, such as on the International Space Station (ISS), require high cognitive and motor performance during long-duration and specific upper-body workload with little margin for error. It is well known that increased cardiovascular demands interact with cognitive performance, but no specific knowledge exists about EVA's special requirements. Because the underwater environment is already established for EVA-training, this study investigated the effects of a simulated EVA underwater and exercise intensity on cognitive performance by testing executive functions inhibition (Eriksen Flanker task) and switching (Number-Letter task). METHODS: In a counterbalanced crossover design, 16 divers (age: 28 years (2.4); 8 females) performed two conditions in 3-5 m water submersion (i.e., EVA; Inactivity (INACT)). During EVA, participants performed 30 min of moderate-intensity, followed by 30 min of high-intensity upper-body exercise intervals paired with cognitive-motor tasks that are typically performed during an EVA training. During INACT, participants remained in a submerged and neutrally buoyant position. Both conditions included cognitive testing at pre, mid (after the first 30 min), and post (after the second 30 min) on an underwater functionally tablet computer. Typical scores for task performance such as reaction times (RT) and response accuracy (ACC) were calculated for both tasks. RESULTS: Task ACC was significantly lower during EVA compared to INACT for inhibition (post: p = 0.009) and switching (mid (p = 0.019) and post (p = 0.005), whereas RTs for inhibition were significantly faster during EVA (p = 0.022; ηp² = 0.320). RTs for switching were generally slower during EVA but showed a significant improvement over time (p < 0.001; ηp² = 0.628) for both conditions. CONCLUSIONS: These pilot data suggest faster RTs and lower ACC for the executive functions switching and inhibition. Although physical exercise shows overall positive effects on cognitive performance in laboratory-based studies, the specific physical exercise, intensity, duration, and tasks performed during the simulated EVA might differently affect this relationship and needs further investigation.